2018
DOI: 10.11114/jets.v6i3a.3160
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Administrators’ Behaviors That Involves Favoritism on Organizational Opposition

Abstract: Establishment of effective organizations has been the main subject of many researches in recent years. The effectiveness of organizations is directly or indirectly related to many variables. The concepts of favoritism and organizational opposition among these variables aroused the interest of the researcher and in line with the attained sources, it was found out that no researches with regard to these two concepts have been made up until now. We can briefly define favoritism as giving someone priority or grant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Nurses perceived higher favoritism the longer they stayed in a unit. This confirms the finding of Toytok and Uçar 28 that being in the organization for a long time can lead to friendship, which often inadvertently turns into favoritism. Brahms and Schmitt 46 suggested that favoritism is understood depending on who receives it.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nurses perceived higher favoritism the longer they stayed in a unit. This confirms the finding of Toytok and Uçar 28 that being in the organization for a long time can lead to friendship, which often inadvertently turns into favoritism. Brahms and Schmitt 46 suggested that favoritism is understood depending on who receives it.…”
Section: Discussionsupporting
confidence: 88%
“…According to Morgan, 57 unhappy employees can lead to reduced productivity, poor customer service and problems with employee retention. Favoritism breeds negativity, as it feeds organizational opposition 28 . This causes disputes, division, and disruption, and organizational growth is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The act of power used by managers is defined by Weber (2013) as follows: "Power (Macht) is the potential of an individual in a social relationship to realize his will despite the resistance of others" (p.40). Administrators affect their subordinates by using various sources of power and steer the individuals to the desired acts that will realize the objectives of the organization (Toytok & Uçar, 2018). Weber (2013) divided the sources of power that help administrators establish authority over their subordinates into three: rational power, traditional power, and charismatic power.…”
Section: Introductionmentioning
confidence: 99%
“…Özcenay (2017) conducted a study with teachers and school administrators and found that the most preferred power type of administrators was legal power. Toytok and Uçar (2018) stated that the inability of school administrators to use power resources is related to the emergence of perceptions and behaviours related to depression in teachers. Therefore, they emphasized that using the sources of power in the right time and with the right methods has a supportive role in ensure that the school organisation achieves its goals.…”
Section: Introductionmentioning
confidence: 99%